Divergence and Convergence in Enzyme Evolution - Galperin, Michael Y. (American Society for Biochemistry and Molecular Biology, 2012)
Comparative analysis of the sequences of enzymes encoded in a variety of prokaryotic and eukaryotic genomes reveals convergence and divergence at several levels. Functional convergence can be inferred when structurally distinct and hence non-homologous enzymes show the ability to catalyze the same biochemical reaction. In contrast, as a result of functional diversification, many structurally similar enzyme molecules act on substantially distinct substrates and catalyze diverse biochemical reactions. Here, we present updates on the ATP-grasp, alkaline phosphatase, cupin, HD hydrolase, and N-terminal nucleophile (Ntn) hydrolase enzyme superfamilies and discuss the patterns of sequence and structural conservation and diversity within these superfamilies. Typically, enzymes within a superfamily possess common sequence motifs and key active site residues, as well as (predicted) reaction mechanisms. These observations suggest that the strained conformation (the entatic state) of the active site, which is responsible for the substrate binding and formation of the transition complex, tends to be conserved within enzyme superfamilies. The subsequent fate of the transition complex is not necessarily conserved and depends on the details of the structures of the enzyme and the substrate. This variability of reaction outcomes limits the ability of sequence analysis to predict the exact enzymatic activities of newly sequenced gene products. Nevertheless, sequence-based (super)family assignments and generic functional predictions, even if imprecise, provide valuable leads for experimental studies and remain the best approach to the functional annotation of uncharacterized proteins from new genomes.